Clinical Vigilance during Epilepsy Management as Proactively Monitoring Adverse Effects of Sodium Valproate: A Case Report - Jha, Ambika Nand; Ratan, Varsha Gaikwad (Journal of National Institute of Neurosciences Bangladesh, 2025)
Sodium valproate, a first-line antiepileptic drug, is extensively utilized in the treatment of both primary and secondary generalized seizures. Approved by the U.S. Food and Drug Administration (FDA) since 1978, this compound is integral to seizure management. However, clinicians must remain vigilant regarding its potential adverse effects, which can include tremors, Reye-like syndrome, sedation, hepatic toxicity, reduced platelet counts, and pancreatitis. Understanding the pharmacodynamics and safety profile of sodium valproate is crucial for optimizing therapeutic outcomes while minimizing risks in patients requiring long-term antiepileptic therapy. Continuous monitoring is advised to manage and mitigate these side effects effectively. A 19-year-old male student admitted to the emergency department of a teaching hospital with gradually worsening drowsiness, accompanied by nausea and short-lived vomiting. He displayed signs of confusion and altered mental status, including disorganized speech, and complained of severe muscle cramps in his legs. After taking a detailed history from the patient’s representative, it was confirmed that the patient experienced an epileptic seizure six months ago. The patient is currently receiving treatment from a psychiatrist and is prescribed Sodium Valproate at a dosage of 500 mg once daily. The patient's blood was sent for pathological tests, and symptomatic treatment was initiated, which included the administration of normal saline, as well as antiemetics and analgesics. Upon review of the blood report, it was revealed that the sodium level was markedly decreased (86 mEq/L). Considering the clinical literature and the patient's medical history, a provisional diagnosis of drug-induced hyponatremia was established. Clinicians should emphasize the importance of closely monitoring patients taking sodium valproate for hyponatremia and associated complications. Journal of National Institute of Neurosciences Bangladesh, January 2025;11(1):88-91